2019
DOI: 10.1111/are.14290
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of growth requirements and scale‐up cultivation of freshwater algaeDesmodesmus armatususing response surface methodology

Abstract: In order to optimize the optimal cultivation conditions of freshwater algae Desmodesmus armatus for biomass production. In this study, the optimum source of carbon, nitrogen and intensity of light were investigated. Particularly, the variables which are affect the biomass of D. armatus was screened by the Plackett‐Burman (PB) method. Furthermore, the optimized medium composition using central composite design (CCD) of response surface method (RSM) central for D. armatus was reconstituted accordingly to have 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The RSM is an interesting approach for the optimization of biomass and specific metabolites. Over the years, this method has been proven to be an interesting statistical tool for better culture media in strains such as Ankistrodesmus falcatus KJ671624, 48 Auxenochlorella protothecoides , 49 Botryococcus braunii , 24 B. braunii LB572, 50 Chlorella sp., 51 Chlorellaprotothecoides , 52 Chlorella sorokiniana Mb-1, 53 Chlorella vulgaris , 54 C. vulgaris 1803, 55 Chlorococcum oleofaciens , 17 Desmodesmus armtus , 56 Dunaliella salina , 57 C. pyrenoidosa , 58 Scenedesmus sp. ASK22, 59 Scenedesmus obliquus , 60 , 61 and Spirulina sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RSM is an interesting approach for the optimization of biomass and specific metabolites. Over the years, this method has been proven to be an interesting statistical tool for better culture media in strains such as Ankistrodesmus falcatus KJ671624, 48 Auxenochlorella protothecoides , 49 Botryococcus braunii , 24 B. braunii LB572, 50 Chlorella sp., 51 Chlorellaprotothecoides , 52 Chlorella sorokiniana Mb-1, 53 Chlorella vulgaris , 54 C. vulgaris 1803, 55 Chlorococcum oleofaciens , 17 Desmodesmus armtus , 56 Dunaliella salina , 57 C. pyrenoidosa , 58 Scenedesmus sp. ASK22, 59 Scenedesmus obliquus , 60 , 61 and Spirulina sp.…”
Section: Discussionmentioning
confidence: 99%
“…braunii LB572, Chlorella sp., Chlorellaprotothecoides, Chlorella sorokiniana Mb-1, Chlorella vulgaris, C. vulgaris 1803, Chlorococcum oleofaciens, Desmodesmus armtus, Dunaliella salina, C. pyrenoidosa, Scenedesmus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, increasing light intensity appeared to be effective for carotenoid yield. Wang et al 2019 reported that optimized medium composition by Central Composite Design (CCD) for freshwater alga Desmodesmus armatus was stated indicated the nitrate concentration of 0.93 g L -1 under the light intensity of 108 μmol/m 2 s, at 27 °C, at pH 7.00 and air flow rate of 0.50 L/min.…”
Section: Determination Of Carotenoid Concentration and Statistical Analysismentioning
confidence: 99%
“…One available tool is the application of the design of experiments (DoE) [88][89][90][91][92] to improve concentrations of specific metabolites. This type of experiment has been successfully applied to improve the deposition of specific metabolites in algae and cyanobacteria before [93][94][95][96][97][98], especially in the selection of the carbon and nitrogen sources and their specific concentrations. However, to the best of our knowledge, there is no scientific literature on the optimization of culture media for strains from high-mountain environments.…”
Section: Introductionmentioning
confidence: 99%